2013
DOI: 10.2174/1874944501306010011
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Assessment across Homogeneous Specialty Clinics in the Region of Thessaly, Greece

Abstract: Abstract:Background: Hospital care expenditure is the most significant cost driver in the health care sector. Reductions in public hospitals' expenses are among the principal austerity measures included in the memorandum recommendations. However, health policy decision-making seems to be a political rather than a technical issue.Objective: The aim of this paper is to assess performance by using Data Envelopment Analysis(DEA) among homogeneous specialties in the General Medicine(GM) and surgical clinics, across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In Greece, many studies were conducted to measure the efficiency and productivity at the hospital and the clinical level by applying the DEA, with the majority of them being input oriented [ 32 , 33 , 36 , 39 , 40 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 79 , 80 , 81 , 82 , 83 ]. Only the studies of Androutsou, et al, in 2011 [ 42 ] and Geitona, et al, in 2013 [ 50 ] were output-oriented, comparing the homogeneous and heterogeneous hospital clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Greece, many studies were conducted to measure the efficiency and productivity at the hospital and the clinical level by applying the DEA, with the majority of them being input oriented [ 32 , 33 , 36 , 39 , 40 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 79 , 80 , 81 , 82 , 83 ]. Only the studies of Androutsou, et al, in 2011 [ 42 ] and Geitona, et al, in 2013 [ 50 ] were output-oriented, comparing the homogeneous and heterogeneous hospital clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in efficiency measurement, using parametric or non-parametric techniques in the hospital sector, have been conducted in several countries, including Greece [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. However, the published bibliography assessing the efficiency at the clinical level by running the DEA [ 50 , 51 , 52 ], has been limited with only a single study examining the combined efficiency and productivity in Greece [ 42 ]. In early 2020, the COVID-19 pandemic was declared by the WHO, urging the need to reallocate resources and recruit personnel efficiently and productively, as one of the main measures to respond to this health system crisis.…”
Section: Introductionmentioning
confidence: 99%
“…DEA analysis has been widely used in other economic sectors since 1957 by Farrell (1957) as organisations have struggled to improve productivity and efficiency. DEA has a long history with lots of important publications in measuring efficiency of hospitals and clinics (Caves et al, 1982;Lovell, 1996;Cook and Seiford, 2009;Charnes et al, 1978;Färe et al, 1994;Coelli et al, 2005;Coelli and Perelman, 1996;Hollingsworth et al, 1999;Färe et al, 1989;Halkos and Tzeremes, 2010;Ancarani et al, 2009;Maniadakis et al, 2007;Androutsou et al, 2011;Staat, 2006;Geitona et al, 2013;Pulina et al, 2010;Khushalani and Ozcan, 2017;Steinmann and Zweifel, 2003;Leleu et al, 2014;Samut and Cafrı, 2016;Moran and Jacobs, 2013;Linna et al, 2006;Varabyova and Schreyögg, 2013;Medina et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The findings demonstrated that technical efficiency was indeed improved but, scale efficiency remained the same. Androutsou et al [7,19] measured the performance in seven homogenous specialty clinics across all National Health System hospitals in the Regional Health Authority of Thessaly, over the period 2002-2006 with Malmquist Index.…”
Section: Literature Reviewmentioning
confidence: 99%